Kinematic linkage between internal zone extension and shortening in more external units in the NW Alps - Wheeler, J.; Reddy, Steven; Cliff, R. (Geological Society of London, 2001)
In the Alps a major extensional shear zone unroofed eclogites in its footwall from 30 kbar to c. 10 kbar, implying of the order of 60 km of relative vertical movement in the period 45-36 Ma. The horizontal component of divergence was of the order of 100 km. We use the foreland basin sedimentary record to prove that the extension was contemporaneous with thrusting in units structurally beneath the eclogites (the Brianconnais and/or External Zones). This thrust-related convergence during that time period was of the order of 44-56 km and therefore of the same order of magnitude as internal zone divergence. Extension may have been driven by internal density contrasts. Buoyant continental crust underneath the mafic eclogites, or dense subducted slab offset from the orogen, can induce extension. Any dynamic model must account for the comparable magnitudes of extension and shortening in adjacent parts of the orogen: relative plate motions in the period 45-36 Ma played a subsidiary role.